Circuit listening : Chinese popular music in the global 1960s - Jones, Andrew F. (University of Minnesota Press, 2020)
"This manuscript seeks to write China back into the narrative about the explosion of new forms of popular music globally in the 1960s. In the context of China and Taiwan, new aesthetic forms of music emerged and circulated via circuits of exchange between urban and rural, from the radio circuits that linked major urban centers to the West to the "closed circuits" of socialist media across rural China"--